Toward Normative Expert Systems: Part I The Pathfinder Project - Heckerman, D. E.; Horvitz, E. J.; Nathwani, B. N. (Methods of Information in Medicine, 1992)
Pathfinder is an expert system that assists surgical pathologists with the diagnosis of lymph-node diseases. The program is one of a growing number of normative expert systems that use probability and decision theory to acquire, represent, manipulate, and explain uncertain medical knowledge. In this article, we describe Pathfinder and our research in uncertain-reasoning paradigms that was stimulated by the development of the program. We discuss limitations with early decision-theoretic methods for reasoning under uncertainty and our initial attempts to use non-decision-theoretic methods. Then, we describe experimental and theoretical results that directed us to return to reasoning methods based in probability and decision theory.
Keywords: Expert Systems; Decision Making; Diagnosis; Probability Theory; Decision Theory; Artificial Intelligence; Pathology